Early results of the breast cancer conservative therapy - Nowicki, Andrzej; Krajewski, Edward; Maruszak, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2006)
Introduction: There are 10.000 new cases of breast cancer observed every year, BCT operation is performed on only 5% of the patients in Poland, and on 50-70% of the patients in the Western Europe. This is a very serious social problem because of treatment methods used today due to physical disability and psychological shock in women. The aim of the thesis is an early assessment of breast cancer treatment of women with the conservative method. Material and methods: From 1999 to 2004 there were 75 patients treated with the BCT mode and 75 patients treated with Patey’s operation mode in the Specialistic Municipal Hospital in Toruń. All the patients were treated in accordance to the standards recommended for a given operation. The average age of the patients after the BCT was 54 years (from 33 to 88 years). The average age of the patients after the Patey’s operation was 59 years (from 37 to 85). Subsequently, the patients were subjected to control examinations in the Hospital Outpatient Oncological Clinic. The average time of observation of the patients after the BCT was 44 months, and after the Patey’s operation was 43 months. Results: Tumors in right breast were observed in 32 and 43 of 75 patients which have been classified for BCT. Cancer was observed in upper outer breast quadrant in 51% of patients. The smallest number of tumor was observed in inner lower breast quadrant. Ductile type of infiltrating cancer was diagnosed in most cases (above 70% in both research groups). In most patients from both research groups have breast cancer at pT1c stage, 40 (53%) and 36 (48%), accordingly and at pT2 stage, 17 (23%) and 24 (32%), accordingly. In 19 (20% of patients after BCT and 30 (40%) of patients after Patey’s surgery histopathological metastatic changes were observed in auxillary nodes. Complications of after surgery wounds occurred after Patey’s surgery and swelling of the hand occurred in 2 patients after BCT and 2 patients after Patey’s surgery. In 4 cases after the BCT and in 2 cases after the Patey’s operation local recurrences occurred. Remote metastases were observed in 6 patients after the BCT as well as in 6 patients after breast amputation. Conclusions: The average 44 month long survival was obtained in 94.7% of women after the BCT and in 96% of women after the Patey’s operation and survival free from disease recurrence was observed in 89.4% of all cases. Results of conservative treatment are comparable to those of amputation and correlate with data from other centres.